The nuclear option ; I wanna be in America ; The making of an image [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
The Philippines suffered a setback in its fight against Westinghouse when it lost the bribery suit it field against the Marcoses. A Filipino-American immigration expert and the U.S. Consul-General warns the illegal activities of Filipinos going abroad. A look at the works of Filipino fashion photographers.
The Nuclear option (17 min.) -- I wanna be in America (16 min.) -- The making of an image (12 min.)
VHS.
Keywords: Bataan Nuclear Power Plant; Nuclear power plants -- Philippines -- Bataan; Commercial photography -- Philippines; Photographers -- Philippines; Filipinos -- United States; Philippines -- Emigration and immigration -- Social aspects; United States -- Emigration and immigration